(untitled) (Revista INTEREDU11, 2021)
This article explores how the Chilean Credit Transfer and Accumulation System (SCT–Chile, for its acronym in Spanish) has been put into effect in undergraduate programs of education and health sciences, at Universidad de Los Lagos, Osorno Campus. This study applies a mixed-method approach consisting of qualitative and quantitative data-collection techniques. As a result, it is possible to claim that though there is a high degree of heterogeneity regarding the form this process has taken across these programs, the resources available for its implementation, and the support received by the committees appointed to carry out this process, there is more to be done when it comes to following-up and monitoring the implemented innovations.